Victim Ambiguity: Bystander Intervention and Sexual Assault in the College Drinking Scene. Issue 4 (2nd April 2016) - Pugh, Brandie; Ningard, Holly; Ven, Thomas Vander; Butler, Leah
ABSTRACT: Alcohol-related sexual assault is the most common form of sexual victimization on college campuses. Bystander intervention has been suggested as effective in preventing sexual assault, but its usefulness in sexual assaults that involve alcohol in particular has not yet been examined. The current study draws from intensive interviews with 30 undergraduates at a large Midwestern university to understand how students' perceptions about sexual victimization and alcohol use affect their bystander behavior. Findings suggest that in alcohol-involved situations, the ambiguity of whether the woman is at risk and her perceived worthiness are significant barriers to intervention. Policy implications are discussed.